Peran Organisai Profesi Advokat terhadap Anggotanya yang Berhadapan dengan Hukum - Kharunnisa Kharunnisa; Chantika Andini Saragih; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
This study aims to determine the role of Advocate Organizations in maintaining the dignity and dignity of Advocates who are in conflict with the law. Sociologically, the Advocate profession is a profession that is free and independent and is responsible for law enforcement. It also aims to find out the provisions regarding advocate immunity rights to what extent these rights are implemented. The Advocate Law recognizes the limited right of advocate immunity, namely regulated in Article 14, Article 15, Article 16 of the Advocate Law Number 18 of 2003 Concerning Advocates, by recognizing and guaranteeing the protection of Advocates in non-litigation actions carried out in good faith both and for the benefit of the client's defense inside and outside the court. The approach used in this study is a normative juridical approach. The results of this study explain that professional organizations are present in protecting the Advocate profession, especially related to Advocate immunity rights. Keywords: Advocate Organization, Advocate Immunity Right.